La migliore offerta - Rush, Geoffrey 1951-; Sturgess, Jim 1978-; Hoeks, Sylvia 1983-; Sutherland, Donald 1935-2024 (Warner Home Video Italia, 2013)
"A story centered on an eccentric art auctioneer and his obsession with an heiress/collector"--IMDb
Originally produced as a motion picture in Italy in 2012; released in the United States as The best offer. - DVD; PAL; region 2; aspect ratios 2.35:1 and 16:9; Dolby Digital 5.1. - Special content: Filming "The best offer."
Keywords: Man-woman relationships / Drama; Obsessive-compulsive disorder / Drama; Art / Collectors and collecting / Drama; Auctioneers / Drama; Kunst; DVD-Video